Social Dialog as a Model of Mission in Plural Society - Timotius Timotius; Sutrisno Sutrisno; Bobby Kurnia Putrawan (Sekolah Tinggi Theologia Nazarene Indonesia, 2022)
This study was conducted to answer the criticism of the dialogue process in a pluralistic society. There is a dualism that separates mission and dialogue (social dialogue and spiritual dialogue). In this regard, there is a concern that social dialogue will have a missiological tendency which will affect the faith of others. Thus, there is no need for social dialogue. This article aims to explain that social dialogue is not harmful because social dialogue does not always affect one's faith. On the other hand, social dialogue can be an important model in this plural society. The study in this study was conducted using a qualitative descriptive method with a literature research approach. The research was conducted by investigating primary and secondary sources to find out the esense of social dialogue. The results of this study show that social dialogue is not harmful because social dialogue is an unavoidable fact. The incarnation of Christ forms the basis of dialogue for Christians to live in the midst of pluralism